Goniometric evaluation of both forelimbs and hind limbs in two species of Neotropical monkeys. Issue 6 (19th July 2014) - Conceição, Renato Tavares; Rahal, Sheila Canevese; Melchert, Alessandra; Bortoloni, Zara; Teixeira, Carlos Roberto; Imbeloni, Aline Amaral; Monteiro, Frederico Ozanan Barros
Abstract Background The aim of this study was to evaluate the goniometric measurements of the forelimb and hind limb joints in two species of Neotropical primates maintained in captivity. Methods Eighteen intact monkeys organized into two groups were studied: Group 1–9 brown howlers (Alouatta fusca), and Group 2–9 tufted capuchins (Sapajus apella). Results Significant differences were observed in the maximum flexion of the shoulder, elbow, carpus, stifle, and tarsus (G1>G2); maximum extension and abduction of the shoulder (G1<G2); maximum extension (G1>G2) and adduction (G1<G2) of the carpus; and maximum extension, abduction and adduction of the hip (G1>G2). The ROM was significantly different in all joints: shoulder (G1<G2), elbow (G1<G2), carpus (G1>G2), hip (G1>G2), stifle (G1<G2), and tarsus (G1<G2). Conclusions A. fusca and S. apella maintained in captivity have significant differences in the goniometric measurements of both forelimb and hind limb joints, primarily in maximum flexion and ROM.